Analisis Implementasi Standar Akuntansi Pemerintah Berbasis Akrual pada Dinas Pariwisata Kota Solok - Nikko Prasetya, Muhammad; Indrayeni, Indrayeni (Borobudur Accounting Review, 2021)
This study aims to determine the application of accrual-based government accounting standards at the Solok City Tourism Office. The method used is descriptive qualitative. The results showed that the City of Solok Tourism Office began to apply an accrual basis to accounting in 2018. This is due to the lack of competent human resources at the agency. At this time, the City of Solok Tourism Office has not fully used SIMDA. The Dinas still uses a manual system for recording. Not optimal use of SIMDA is due to inadequate network at the agency. This research is expected to contribute to the application of accrual accounting to the government. With many obstacles encountered in implementing accrual basis in government, it is necessary for the government to prepare competent human resources and provide more training to these human resources so that the implementation of accrual accounting in the government becomes even better.